Reevaluating the Role of Urban Foraging in Tokyo Metropolitan Areas - Sakakibara, Mako (Departemen Sosiologi Universitas Gadjah Mada, 2024)
Urban Foraging (UF) has gained increasing attention in recent years as a means of engaging with nature in urban environments and as an adaptive strategy for urbanization and green space reduction. While research on UF has been conducted in Western countries, studies in Japan remain scarce. This study aims to analyze UF practices and their impact in Tokyo metropolitan area. Through interviews with UF practitioners and local government officials, as well as fieldwork in Tokyo and surrounding areas, this study reveals key patterns in UF engagement. Findings indicate that individuals who forage more frequently tend to collect a greater variety of resources, including plants, fungi, and even engage in hunting and fishing. Common foraging sites include rivers, parks, and vacant lots, with food being the primary motivation. Many practitioners have childhood foraging experiences, and social media and community networks serve as important sources of knowledge. Furthermore, UF appears to influence practitioners' perceptions of nature. From an administrative perspective, many municipalities prohibit foraging in parks, although some adopt a more flexible stance. The study highlights the emergence of ethical considerations and informal regulations among urban foragers. Through food consumption, practitioners develop a deeper awareness of their relationship with urban nature. This study suggests that UF could foster novel human-nature relationships and enhance urban green space utilization. However, further research is needed to examine gender, socioeconomic differences, homelessness, foreign urban foragers, commercial exploitation, and overforaging concerns.